EFFECT OF LONG-TERM STORAGE OF CAJEPUT LEAVES (Melaleuca Leucadendron Linn) ON OIL QUALITY FROM ROTE NDAO REGENCY - Manek, Luisa; Adrin; Tamonob, Melintong (Jurnal Belantara, 2024)
Cajeput oil is one of the non-timber forest products produced by distilling Cajeput leaves of the Melaleuca leucadendron Linn type. Several factors influence the quality of Cajeput oil, including filling the leaves in the kettle, tree variety, where the Cajeputi grows, storage of the leaves, distillation techniques, distillation temperature, and age. This research aims to determine the effect of storage time for raw materials on the yield, refractive index, and sineol content of Cajeput oil and the best time to store refining raw materials before distillation. The raw materials for distillation are taken from Rote Ndao Regency and then stored for varying lengths of time ranging from 3 days, 4 days, and 5 days, and the distillation method used is the boil method. The research results showed that the highest average per parameter was obtained after 5 days of storage with a yield value of 2.43%, a refractive index of 1.45%, and a sineole content of 56.67%. The average weight of cineole content and refractive index is included in the Indonesian National Standard (SNI 06-03954-2014).